Finite-frequency H∞ control for offshore platforms subject to parametric model uncertainty and practical hard constraints - Kazemy, Ali (2020)
In this paper, the problem of finite-frequency H∞ controller design for offshore platforms has been addressed. In order to comply with practical requirements, model uncertainties and physical hard constraints such as actuator saturation, maximum allowable displacement of the platform, and maximum deflection of active mass damper (AMD) and the platform deck have been considered and incorporated into the controller design. Then, based on the generalized Kalman-Yakubovic-Popov (KYP) lemma, sufficient conditions have been established in the form of linear matrix inequalities (LMIs) to ensure the existence of the finite-frequency H∞ controller. Finally, a simplified platform model is utilized to illustrate the effectiveness of the proposed method.